2014
DOI: 10.2355/isijinternational.54.533
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Concentric Solidification Technique for High-Temperature Laser-Scanning Confocal Microscopy

Abstract: We present further developments and enhancements of the concentric solidification technique for high-temperature laser-scanning confocal microscopy. These recent enhancements include an automated in-situ determination of phase fractions during solidification using purposely developed image processing software, more accurate temperature calibration, reproducibility tests as well as close coupling of the experimental results with computational simulations. In the present study, the newly developed capabilities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…3(a)). As is found by Slater et al 23) and other scholars 12,24) , the dark particles are the direct signs of the carbonitrides. Segregation of solute atoms usually occurs at the austenite grain boundary, which accelerates the precipitation of the carbonitrides and dark particles.…”
Section: In-situ Characterization Of Secondary Phase Precipitationsupporting
confidence: 51%
“…3(a)). As is found by Slater et al 23) and other scholars 12,24) , the dark particles are the direct signs of the carbonitrides. Segregation of solute atoms usually occurs at the austenite grain boundary, which accelerates the precipitation of the carbonitrides and dark particles.…”
Section: In-situ Characterization Of Secondary Phase Precipitationsupporting
confidence: 51%
“…The reaction was not controlled by carbon diffusion but rather by a massive transformation or solidification of the γ phase directly from the liquid. Griesser et al [ 17–19 ] revealed the mechanism of peritectic transformation in the equilibrium of peritectic steels by circular solidification experiments using HT‐CLSM. Agarwal et al [ 20 ] investigated the solidification process of transformation‐induced plasticity steels using HT‐CLSM and revealed the mechanism of phase‐change‐induced crack formation.…”
Section: Introductionmentioning
confidence: 99%
“…Dippenaar used HTCLSM to study the phase transformation processes of slag, flux, and steel during heating and cooling, correlating them with theoretical predictions [ 22 , 23 , 24 ]. He developed a concentric solidification technology based on high-temperature confocal experiments, which can be used to study the surface tension, interface morphology, and high-temperature physical properties of metallic materials [ 25 , 26 ]. Hiroyuki et al discussed the mechanism of trapping and repelling inclusions using a moving solid–liquid interface during the solidification of Al-Sikilled steels [ 27 ].…”
Section: Introductionmentioning
confidence: 99%